PENGARUH FASILITAS SELF CHECK-IN TERHADAP KEPUASAN PENUMPANG MASKAPAI CITILINK PADA MASA ARUS MUDIK LEBARAN DI BANDAR UDARA INTERNASIONAL HALIM PERDANAKUSUMA JAKARTA - Lu`luatul Fuadah; Arif Fakhrudin (Jurnal Manajemen Dirgantara, 2024)
It is hoped that the self-check-in facility can reduce queues at check-in counters and facilitate mobility during the Eid homecoming flow. The aim of this research is to determine the effect of self check-in facilities on Citilink Airlines passenger satisfaction during the Eid homecoming flow at Halim Perdanakusuma International Airport, Jakarta. This research is quantitative research using primary data in the form of surveys (questionnaires) for data collection and secondary data in the form of literature studies to connect theories. The population in this study were Citilink airline passengers who had self-check-in or had used the self-check-in facility provided by Citilink Airlines at Halim Perdanakusuma International Airport, Jakarta. A sample of 100 respondents was taken using a simple random sampling technique and using the Solvin formula. The data was then analyzed using instrument tests, simple linear regression analysis, coefficient of determination (R²) test, and T/significant test. The results of the analysis state that Ho is rejected and Ha is accepted, which means there is a significant influence between these two variables, and the self check-in facility variable has a significant positive effect on the passenger satisfaction variable. The influence of self check-in facilities on passenger satisfaction in this study was 74.6%, while the remainder was influenced by other factors or variables not used in the research.